53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1155
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Unsteady Combustion Phenomena in a University Scale Rocket Combustor

Abstract: We investigate the steady and unsteady flame properties in a moderate pressure, single shear coaxial injector operated with gaseous oxygen/hydrogen and how they relate to the underlying fluid dynamic properties of the flowfield. Under a certain range of conditions, we observe strong modifications of the flame structure as a result of a low-amplitude thermoacoustic instability that develops naturally under fuel-lean conditions. In particular, we observe a periodic evolution of the flame front where ejection eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Table 1 summarizes the low pressure cases for both configurations up to the stability limit. In one of our previous works concerning non-reacting mixing experiments, 16 we found that the (inner-to-outer) momentum flux ratio J = SR 2 was an important parameter in delineating the steady and unsteady cases. R = v i /v o and S = ρ i /ρ o are the (inner-to-outer) velocity and density ratios respectively.…”
Section: Comparison Of Instability Limitsmentioning
confidence: 74%
“…Table 1 summarizes the low pressure cases for both configurations up to the stability limit. In one of our previous works concerning non-reacting mixing experiments, 16 we found that the (inner-to-outer) momentum flux ratio J = SR 2 was an important parameter in delineating the steady and unsteady cases. R = v i /v o and S = ρ i /ρ o are the (inner-to-outer) velocity and density ratios respectively.…”
Section: Comparison Of Instability Limitsmentioning
confidence: 74%
“…In an attempt to link the observed behavior to possible causes (e.g., local fluctuations of fuel/oxidizer, equivalence ratio, etc), we have considered the properties, and in particular the mixing field, of variable-density, turbulent non-reacting coaxial jets. The results of this part of the study are described more in detail in our companion work; 22 here we report only the main result. From mixture measurements of the flowfield generated by coaxial injection of different molecular weight (i.e., different initial density) fluids we identify the formation of what are referred to as "side jets" under certain coaxial injection configurations.…”
Section: Combustion Instability and Side-jet Formation In Variable-dementioning
confidence: 92%
“…More details on the experimental configuration use for the non-reacting, variable-density experiments is documented in the companion work. 22 For all cases in the present study, the inner tube has an inner diameter D i of 3.66 mm and an outer diameter of 4.76 mm, and the annulus has a diameter D o of 6.73 mm.…”
Section: A Test Apparatusmentioning
confidence: 99%
See 1 more Smart Citation